Presence of Hartmanns Pouch in Human Gallbladder (Bangladesh Journal of Anatomy, 2013)
Context: Hartmanns pouch is an out-pouching of the wall of the gallbladder, at the junction of the neck of the gallbladder and the cystic duct. It may be a site where gall stone impacts, which leads to mucocele of gallbladder. So its identification is useful in delineating biliary anatomy while performing a cholecystectomy. Objective: To identify the presence of Hartmanns pouch in human gallbladder. Study Design: A cross-sectional type of study. Place and period of study: The study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka from July 2008 to June 2009. Materials: 70 postmortem gallbladder were collected from unclaimed dead bodies that were under examination in the morgue of the Department of Forensic Medicine, Dhaka Medical College, Dhaka. Methods: Formalin fixed gallbladder was washed with plain tap water to remove excess formalin and was kept on metallic tray. On observation Hartmanns pouch in gallbladder was detected and noted. Results: In the present study 70 cadavers gallbladder were observed carefully in the neck region for Hartmanns pouch. The Hartmanns pouch was detected in 4 cases out of 70 (5.7%). Conclusion: Further studies to find out the gross anatomy and histological study of Hartmanns pouch is recommended. DOI: http://dx.doi.org/10.3329/bja.v10i2.17283 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 57-58